Impact of Gamification and Interactive Language Learning Platforms on Engagement and Proficiency in English Language Education - Roseni, Emilda; Muho, Anita (Journal of Education Culture and Society, 2024)
Aim. This paper aims to quantify and assess the level of satisfaction and the impact associated with using gamification and interactive learning platforms in the context of English language learning among students. In this research paper, we delve into the exciting domain of gamification and interactive language learning platforms to uncover their potential to enrich student engagement and proficiency in English language education. Method. Through a rigorous quantitative approach, we meticulously scrutinize the effects of infusing gamified elements and interactive platforms into the fabric of English language instruction. The sample consists of 59 foreign language students (English and German) enrolled in Bachelor and Master degree programs at Aleksandër Moisiu University, Durrës. The selection criteria were based on the students’ availability and willingness to participate during the period from January to March 2024. This method ensures the inclusion of a diverse group of students within the specified timeframe. Results and conclusion. By delving deep into the quantitative data gleaned from participants’ performance metrics, our study offers concrete, evidence-based insights into the effectiveness of gamification and interactive platforms in fueling language acquisition and fostering learner motivation.